(NtEKTONOFACII I GEOLOGIQ RUDNYH OB_EKTOW (B/s - (NmATWIENKO(B, (Nw(B.(Nn(B.s; (NaBDULIN(B, (NaJTMUHAMED aBDULLAEWI^s; (NiNSTITUT GEOLOGI^ESKIH NAUK IM(B. (Nk(B.(Ni(B. (NsATPAEWA an kAZssrs ((NaLMA(B-(NaTA (B:s (NnAUKA(B. (NkAZssr(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 199-206 (170 (NNAZW(B.)s
(NaWT(B. (NUKAZANY W OGL(B.s
Keywords: (NrUDNYE MESTOROVDENIQ (B- (NtEKTONIKAs; (NfACIIs